1996
DOI: 10.1183/09031936.96.09040733
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and delayed effects of nitrogen dioxide exposure at an ambient level on bronchial responsiveness to histamine in subjects with asthma

Abstract: Immediate and delayed effects of nitrogen dioxide exposure at an ambient level on bronchial responsiveness to histamine in subjects with asthma. V. Strand, P. Salomonsson, J. Lundahl, G. Bylin. ERS Journals Ltd 1996. ABSTRACT: The time-kinetics of NO 2 induced effects on bronchial responsiveness are poorly known as most observations have been made shortly after exposure. The aim of this study was to measure nonspecific bronchial responsiveness, lung function and inflammatory markers at different times after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…Animal studies have provided evidence that the particulate fraction of DE is able to cause an increase in airway responsiveness [28], but to the best of the authors9 knowledge, there are no previous experimental data concerning particulate pollution and hyperresponsiveness in humans. Regarding the gaseous phase of DE, some studies have reported an immediate increase in airway responsiveness following exposure to NO 2 [29,30], whereas other studies have not [31]. Most studies have been designed to explore the immediate and early effects of NO 2 and it is not clear from the literature whether NO 2 is able to induce a sustained increase in airway responsiveness.…”
Section: Discussionmentioning
confidence: 97%
“…Animal studies have provided evidence that the particulate fraction of DE is able to cause an increase in airway responsiveness [28], but to the best of the authors9 knowledge, there are no previous experimental data concerning particulate pollution and hyperresponsiveness in humans. Regarding the gaseous phase of DE, some studies have reported an immediate increase in airway responsiveness following exposure to NO 2 [29,30], whereas other studies have not [31]. Most studies have been designed to explore the immediate and early effects of NO 2 and it is not clear from the literature whether NO 2 is able to induce a sustained increase in airway responsiveness.…”
Section: Discussionmentioning
confidence: 97%
“…In healthy individuals, small increases in nonspecific airway hyperresponsiveness have been reported following short-term (1-3 hour) exposure to NO 2 in the range 1.5-2.0 ppm (Mohsenin, 1987;Frampton et al, 1989). In asthmatics, the data on nonspecific hyperresponsiveness to NO 2 suggests a sensitizing effect between 0.2 ppm and 0.6 ppm, though the responses, where significant, were small and unlikely to be of clinical significance (Bylin et al, 1985;Mohsenin, 1987;Strand et al, 1996). A limited number of studies have evaluated airway hyperresponsiveness in asthmatics at multiple NO 2 concentrations, and the results of these studies do not support a clear concentration-response relationship between 0.1 ppm and 0.5ppm (Bylin et al, 1988;Roger et al, 1990;Tunnicliffe, Burge & Ayres, 1994).…”
Section: Chamber Studiesmentioning
confidence: 92%
“…The lagged-day effects, usually up to 5 days, notwithstanding the variation among the cities, indicate that the exacerbation of asthma develops over several days as the inflammation progresses in the airways of susceptible individuals. There is also laboratory-based evidence that the increase in bronchial responsiveness of asthmatics after exposure to NO 2 may be delayed, suggesting that there is a period when other triggers can provoke attacks of asthma [19]. …”
Section: Discussionmentioning
confidence: 99%